Association between prediabetes diagnosis and body mass index trajectory of overweight and obese adolescents. Issue 5 (15th May 2020) - Vajravelu, Mary Ellen; Lee, Joyce M.; Shah, Rachana; Shults, Justine; Amaral, Sandra; Kelly, Andrea
Abstract: Background: Prediabetes awareness in adults has been associated with improved weight management. Whether youth with prediabetes diagnosis experience similar improvements is unknown. Objective: To investigate the association between prediabetes identification and body mass index (BMI) trajectory in overweight and obese adolescents. Subjects: Youth who were followed longitudinally in a large academic‐affiliated primary care network and who were overweight/obese while 10 to 18 years old. Methods: Retrospective cohort study. Subjects were categorized as "screened" if at least 1 hemoglobin A1c (HbA1c) result was available. Time series analysis was used to determine the difference in difference (DID) in BMI Z‐score (BMI‐Z) slope before and after HbA1c between: (a) screened youth found to have prediabetes‐range HbA1c (5.7%‐6.4%, 39‐46 mmol/mol) versus normal HbA1c and (b) screened versus age‐matched unscreened obese youth. Results: A total of 4184 (55.6% female) screened subjects (median follow‐up 9.7 years) were included. In which, 637 (15.2%) had prediabetes‐range HbA1c. Prediabetes was associated with a greater decrease in BMI‐Z slope than normal HbA1c (DID: −0.023/year [95% CI: −0.042 to −0.004]). When compared to age‐matched unscreened subjects (n = 2087), screened subjects (n = 2815) experienced a greater decrease in BMI‐Z slope after HbA1c than unscreened subjects at a matched age (DID: −0.031/y [95% CI ‐0.042 to −0.021]). Conclusions: BMI‐Z trajectory improved more among youth with prediabetes‐range HbA1c but also stabilized in screened youth overall. Prospective studies are needed to identify provider‐ and patient‐level drivers of this observation.